Quality of complete feed wafer supplemented with different plant protein sources for small ruminants - Gerson Frans Bira; Azor Yulianus Tefa; Maria Magdalena Kolo; Cornelis Astridino Nitbani; Deni Yonathan Lulu; Agustinus Akoit (Universitas Sebelas Maret, 2024)
Objective: This study aimed to assess the quality of complete feed wafers with different plant protein sources for a feed of small ruminants.Methods:The research was conducted in May-September 2022. The research method used a completely randomized design (CRD) with 4 treatments and 4 replications. The method used in this study was Completely Randomized Design (CRD) with 4 treatments, namely R0 = Wafer with an animal protein source (Fish meal) (Control), R1 = Wafers with protein source Sesbania grandiflora, R2 = Wafers with protein source Gliricidia sepium. R3=Wafer with protein source Leucaena leucocephala.The research variables consisted of physical quality (moisture content, wafer density, specific gravity, water absorption) and nutritional quality (dry matter, organic matter, crude protein, crude fat, crude fiber, and nitrogen free extracts). Data analysis according to the Analysis of Variance procedure using SPSS version 21.Results:The results showed that the use of plant protein sources had no significant effect (P>0.05) on water content and wafer density but had a significant effect (P<0.05) on specific gravity and water absorption capacity. The use of plant protein sources can increase the value of water content, wafer density, and specific gravity and reduce water absorption capacity. Meanwhile, the crude protein (CP) content of the wafer had no significant effect (P>0.05) and produced the same value as using fish meal. Other nutritional variables had a significant effect (P<0.05) such as DM, OM, EE and NFE which increased and CF decreased on the use of plant protein sources in making feed wafers compared to the use of fish meal.Conclusions: It was concluded that the use of legumes Sesbania grandiflora, Gliricidia sepium, and Leucaena leucocephala as a source of vegetable protein in wafers could replace fish meal. The three types of legumes had the same effect on the physical and nutritional quality of the resulting product.